Pemerintah Dalam Menyusun Kebijakan Pengawasan Media Sosial Dan Teknologi Digital - Nur Fitriani Rezki.HS; Agung Indra Wijaya; Nur Riswandi Marsuki (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research delves into the impact of scientific advancement on both governmental and private sectors, emphasizing the critical role of Public Relations (PR) in governance and corporate realms. Information technology, particularly the internet and social media, serves as the primary means for public information access. It highlights the significance of public information transparency based on legal regulations, along with social media's role in facilitating public participation concerning public policie. The research methodology includes literature reviews, case studies, expert interviews, and community surveys. Findings emphasize the government's role in supervising social media and digital technology to ensure their safe, fair, and just use. The research also underscores the importance of political participation, whether conventional or online, in governmental policy determination. A case study concerning the role of Facebook in disseminating information by the Faculty of Tarbiyah and Education at IAIN Kendari constitutes a pivotal part of this discussion.